Clustering Based Compress Data Cube Algorithm - Zhijun Xie; Mingxing Nie; Tongsen Wang (World Congress on Software Engineering, 2009)
In this paper, we present a novel clustering based technique to build an approximate compressed data cube and using this compressed data cube to provide answers to queries directly. Results of experiments on the effectiveness of Compact Cube are presented, using both synthetic and real-world data. The results indicate that the proposed Compress Cube can efficiently reduce the cube size. Through comparing the algorithm with some other algorithms, we can conclude that the compact cube is more efficient than others.